2005
DOI: 10.1186/1743-422x-2-69
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine is a potent inhibitor of SARS coronavirus infection and spread

Abstract: Background: Severe acute respiratory syndrome (SARS) is caused by a newly discovered coronavirus (SARS-CoV). No effective prophylactic or post-exposure therapy is currently available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
1,144
0
41

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,607 publications
(1,194 citation statements)
references
References 26 publications
9
1,144
0
41
Order By: Relevance
“…When added extracellularly, chloroquine enters in acidic, low pH organelles, such as endosomes, Golgi vesicles, and lysosomes where it is protonated and concentrated. Chloroquine can affect virus entry in many ways, inhibiting pH-dependent fusion of viral particles or altering the glycosylation of cellular receptors (38). We showed that pretreated cells are resistant to infection by CHIKV, suggesting that chloroquine essentially affects either the pH-dependent fusion or the complex glycosylation of a cellular receptor.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…When added extracellularly, chloroquine enters in acidic, low pH organelles, such as endosomes, Golgi vesicles, and lysosomes where it is protonated and concentrated. Chloroquine can affect virus entry in many ways, inhibiting pH-dependent fusion of viral particles or altering the glycosylation of cellular receptors (38). We showed that pretreated cells are resistant to infection by CHIKV, suggesting that chloroquine essentially affects either the pH-dependent fusion or the complex glycosylation of a cellular receptor.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of a critical His at the cleavage site of PCs was also reported in other substrates such as integrin-␣4 (36), where it was shown to impart a pH dependence on cleavage (36 -38). Indeed, this observation led us originally to propose that alkalinizing agents such as NH 4 Cl and chloroquine may affect the processing of SARS-CoV S-glycoprotein (38). Using the same reasoning, we tested the effect of preincubating the cells with 10 M chloroquine on the ability of furin to process the E3E2 proprotein from 05.115 CHIKV isolate (Fig.…”
Section: Furin-like Convertases and The Processing Of E3e2mentioning
confidence: 99%
“…Recently, a series of in vitro studies have suggested that the antimalarial drug chloroquine may have activity against influenza and other emerging respiratory pathogens 6 , 7 , 8 , 9 . Chloroquine is a lysosomotropic agent that accumulates in the endosomal compartment where it can impair the acidification of the endosome and prevent the conformational changes associated with viral fusion and release into the cytosol.…”
mentioning
confidence: 99%
“…Mechanistic studies against VP35 and possibly other proteins should also be pursued and may be enlightened by the observation that both of these compounds also have reported activity against other viruses. For example, chloroquine is active against human coronavirus OC43 ( in vitro and in infected mice) as well as SARS ( in vitro ) 10, 30, 31 , while amodiaquine also inhibits dengue virus 2 replication and infectivity in vitro 11 .…”
Section: Discussionmentioning
confidence: 99%